Deficits in the Activation of Human Oculomotor Nuclei in Chronic Traumatic Brain Injury - Tyler, Christopher W.; Likova, Lora T.; Mineff, Kristyo N.; Nicholas, Spero C. (Frontiers in Neurology, 2015)
Binocular eye movements form a finely-tuned system that requires accurate coordination of the oculomotor dynamics of the brainstem control nuclei when tracking the fine binocular disparities required for 3D vision. They are particularly susceptible to disruption by brain injury and other neural dysfunctions. Here we report functional Magnetic Resonance Imaging (fMRI) activation of the brainstem oculomotor control nuclei by binocular saccadic and vergence eye movements, and significant reductions in their response amplitudes in mild or diffuse Traumatic Brain Injury (dTBI). Bilateral signals were recorded from a non-TBI Control group (n=11) in the oculomotor control system of the superior colliculi, the oculomotor nuclei, the abducens nuclei and in the supraoculomotor nuclei (SOA), which mediate vergence eye movements. Signals from these nuclei were significantly reduced overall in an dTBI group (n=12) and in particular for the SOA for vergence movements, which also showed significant decreases in velocity for both the convergence and divergence directions.